2021
DOI: 10.1364/ol.422445
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain single photon-excited autofluorescence lifetime for label-free detection of T cell activation

Abstract: Fluorescence lifetime imaging microscopy (FLIM) is a powerful technique, capable of label-free assessment of the metabolic state and function within single cells. The FLIM measurements of autofluorescence were recently shown to be sensitive to the functional state and subtype of T cells. Therefore, autofluorescence FLIM could improve cell manufacturing technologies for adoptive immunotherapy, which currently require a time-intensive process of cell labeling with fluorescent antibodies. However, current autoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…6, A to E). This system is able to detect the autofluorescence of NADPH (reduced form of nicotinamide adenine dinucleotide phosphate) and FAD (flavin adenine dinucleotide) at a single-cell resolution and use their ratios to determine the optical redox ratio (ORR) of the cell population as a measurement of metabolic activity ( 61 , 62 ). This analysis revealed that the DPT population had elevated ORR, indicative of high metabolic activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6, A to E). This system is able to detect the autofluorescence of NADPH (reduced form of nicotinamide adenine dinucleotide phosphate) and FAD (flavin adenine dinucleotide) at a single-cell resolution and use their ratios to determine the optical redox ratio (ORR) of the cell population as a measurement of metabolic activity ( 61 , 62 ). This analysis revealed that the DPT population had elevated ORR, indicative of high metabolic activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further research should explore the effects of media composition and cytokines on CAR T cells with an intact TCR and validate the relationship between OMI measurements and in vivo potency across various CAR T cell and tumor models. Additionally, the current two-photon laser scanning OMI system can be adapted into other configurations such as a single-photon microscope, microfluidic devices ( 51 ), or flow cytometer ( 52, 53 ) to achieve faster speed, automation, and a smaller footprint to better integrate into CAR T manufacturing workflows. These technical efforts will expand the throughput and scope of OMI as a non-invasive, sensitive tool to support the translation of CAR T cell therapy for solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Further research should explore the effects of media composition and cytokines on CAR T cells with an intact TCR and validate the relationship between OMI measurements and in vivo potency across various CAR T cell and tumor models. Additionally, the current two-photon laser scanning OMI system can be adapted into other configurations such as a flow cytometer, microfluidic devices (63), or single-photon microscope (64,65) to achieve faster speed, automation, and a smaller footprint to better integrate into CAR T manufacturing workflows. These technical efforts will expand the throughput and scope of OMI as a noninvasive, sensitive tool to support the translation of CAR T cell therapy for solid tumors.…”
Section: Discussionmentioning
confidence: 99%